Ultrafine Ag/polyoxometalate-doped AgCl nanoparticles in metal–organic framework as efficient photocatalysts under visible light. Issue 45 (2nd November 2016) - Yan, Jian; Zhou, Wen-Zhe; Tan, Huaqiao; Feng, Xiao-Jia; Wang, Yong-Hui; Li, Yang-Guang
Abstract : A new composite material of ultrafine Ag/PW11 O39 -doped AgCl nanoparticles (NPs) encapsulated in a metal–organic framework (NH2 -MIL-101(Al)) was prepared by an incipient wetness impregnation method together with photo-reduction under UV irradiation. Abstract : A new composite material of ultrafine Ag/PW11 O39 -doped AgCl nanoparticles (NPs) encapsulated in a metal–organic framework (NH2 -MIL-101(Al)) was prepared by an incipient wetness impregnation method together with photo-reduction under UV irradiation. The as-prepared composite material (abbr. Ag/POM-AgCl@NH2 -MIL-101(Al)) was characterized by XRD, EDX, SEM, XPS, FT-IR and diffuse reflectance spectroscopy (DRS). By virtue of the coordination interaction between the polyoxometalate (POM) unit and Ag + ion in the K6 [α-AgPW11 O39 ] precursor and the confined cavity of NH2 -MIL-101(Al), the fast reaction between Ag + and Cl − ions was depressed and the over agglomeration of crystalline AgCl was limited. When the partial Ag + ions were reduced into Ag 0 metal in the AgCl NPs under UV irradiation, the resultant ultrafine Ag/POM-AgCl nanoparticles (NPs) possess an average particle size of 3.2 nm in diameter, representing one of the currently smallest Ag/AgCl composite NPs. The catalytic activity of this material was evaluated by the catalytic reduction of 4-nitrophenol and photocatalytic degradation of Rhodamine B (RhB) under visible light irradiation. Compared with its counterparts (Ag/AgCl NPs@NH2 -MIL-101(Al)), the introduction of POM units into the Ag/AgCl composite NPs significantly improved the photocatalytic activity for degradation of RhB under visible light irradiation. A relevant photocatalytic mechanism was proposed.